An Atmosphere of Libération: The Role of Decolonization in the France-Quebec Rapprochement of the 1960s - Meren, David (The Canadian Historical Review, 2011)
Decolonization's impact was by no means restricted to the Global South. It is impossible to understand developments in the Canada-Quebec-France triangle in the 1960s without referring to the discourse, ideas, and examples of anti-colonial resistance that marked international life after the Second World War. In addition to influencing the postwar development of France and Quebec, the decolonization phenomenon figured prominently in the process of rapprochement that developed between them in the post-1945 period. After discussing the global reach of decolonization, this article examines its impact on the Canada-Quebec-France triangle. Particular attention is paid to its intellectual and political consequences, notably the 'Quebec as colony' metaphor and the reimagining of France as a champion of decolonization. The intersection between these two ideas was crucial to the evolution of the France-Quebec relationship.
Keywords: France; Quebec; Québec; Third World; Tiers-monde; de Gaulle; decolonization; décolonisation; postcolonial